Hepatitis C Virus NS2 Protein Is Phosphorylated by the Protein Kinase CK2 and Targeted for Degradation to the Proteasome - Franck, Nathalie (American Society for Microbiology, 2005)
Hepatitis C virus (HCV) nonstructural 2 (NS2) protein is a hydrophobic transmembrane protein, described to be involved in different functions, such as apoptosis inhibition and gene transcription modulation. We investigated here NS2 protein turnover and found that NS2 was rapidly degraded by the proteasome in different cell lines, as in primary human hepatocytes. Since posttranslational modifications can influence protein turnover, we looked for potential phosphoacceptor sites in NS2. Computational sequence analysis in combination with screening of NS2 point mutants revealed that serine residue 168 was critical for degradation. In the quest of a protein kinase for NS2, we identified by sequence analysis that the serine residue 168 was part of a consensus casein kinase 2 (CK2) recognition site (S/TXXE). This motif was highly conserved since it could be found in the NS2 primary consensus sequences from all HCV genotypes. To verify whether CK2 is involved in NS2 phosphorylation, we showed by an in vitro kinase assay that CK2 phosphorylated NS2, as far as this CK2 motif was conserved. Interestingly, NS2 became resistant to protein degradation when the CK2 motif was modified by a single point mutation. Furthermore, inhibition of CK2 activity by curcumin decreased NS2 phosphorylation in vitro and stabilized NS2 expression in HepG2 cells. Finally, we showed in Huh-7.5 replicon cells that NS2, expressed in the context of the HCV polyprotein, was also sensitive to both proteasome-mediated degradation and CK2 inhibitor treatment. We suggest that NS2 is a short-lived protein whose degradation by the proteasome is regulated in a phosphorylation-dependent manner through the protein kinase CK2.